2022
DOI: 10.3390/foods11020212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Processing on Starch Structure, Textural, and Digestive Property of “Horisenbada”, a Traditional Mongolian Food

Abstract: Horisenbada, prepared by the soaking, steaming, and baking of millets, is a traditional Mongolian food and is characterized by its long shelf life, convenience, and nutrition. In this study, the effect of processing on the starch structure, textural, and digestive property of millets was investigated. Compared to the soaking treatment, steaming and baking significantly reduced the molecular size and crystallinity of the millet starch, while baking increased the proportion of long amylose chains, partially dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The resulting product may not be good for diabetics because the use of sucrose coupled with the high sugar content of ripe plantain may contribute in raising the glycemic index (GI) of food and consequently, blood sugar level. Also, many research works have reported on the effect of processing technique on alteration in the starch fraction and digestibility and consequent glycemic properties of food products [28][29][30]. Interestingly, the impact of some treatment techniques on plantain on the digestibility, and control of blood sugar level has been reported by some authors [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting product may not be good for diabetics because the use of sucrose coupled with the high sugar content of ripe plantain may contribute in raising the glycemic index (GI) of food and consequently, blood sugar level. Also, many research works have reported on the effect of processing technique on alteration in the starch fraction and digestibility and consequent glycemic properties of food products [28][29][30]. Interestingly, the impact of some treatment techniques on plantain on the digestibility, and control of blood sugar level has been reported by some authors [31][32][33].…”
Section: Introductionmentioning
confidence: 99%